Computerization of the student assistance scholarships selection process: the IFMG experience (Research, Society and Development, 2021)
Government agencies have been looking for ways to improve their efficiency with the support of technological resources, thus expanding the population's access to various services that, until then, demanded physical presence in certain locations. This article is presented in this context of innovations in electronic government, in particular, because it outlines and presents the results of the computerization project of activities related to the selection process of scholarship students at the Federal Institute of Minas Gerais (IFMG). This is a research that presents a new product from an exploratory experiment conducted as a case study within this institution. The execution of the process with the support of the built Information System generated, as main gains, the reduction of about 51% in the average time of publication of the results of public notices, faster release of financial resources for students with proven socio-economic vulnerability and the optimization of human resources involved with document analysis. Finally, increases in efficiency in the execution of tasks in conjunction with the increase in the satisfaction of those involved are results that must be widely disseminated so that the public administration is more effective in conducting technological innovation projects.